CONSCIOUS MNEMIC ACTIVITY IN LEARNING: EXPERIENCE IN SYSTEMATIZING OF TECHNIQUES - Dieorditsa, Taiana; Voronina, Maryna; Yepifanova, Olga; Tolmachov, Volodimir (Physical and Mathematical Education, 2022)
Formulation of the problem. According to our observations, it is difficult for many students to remember the content of educational texts. In our own pedagogical practice, we provide our students with rational strategies for performing various types of mnemonic activities. Following them, they gradually acquire the skills to consciously manage their own memory. Having set ourselves the goal of developing a strategy for intentional logical memorization of educational texts, we did not find in the psychological literature available to us a systematic description of techniques that mediate this process, and therefore we tried to make such a description ourselves. Based on the interpretation of the strategy as an integrated model of actions aimed at the realization of a complex goal, we asked the following questions: 1) what is the purpose of arbitrary logical memorization of educational texts? 2) what system of techniques makes it possible to achieve it?Materials and methods. The methodological basis of our research is the general theoretical model of memory by G.K. Sereda. Systematization was carried out using the deductive method.Results. The purpose of intentional logical memorization of educational texts has been clarified: the student must firmly consolidate in his own memory the content of the digestible text in certain connections and relations, to be able to reproduce it to the desired extent and within a specified period for adequate use in future activities. The proposed system of intellectual and practical techniques that mediate the process of intentional logical memorization also includes mnemic tasks generated by the performance of this process and a set of mnemic effects that reflect the regular relationships between the effectiveness of memory and those factors that affect it determine. From the multitude of mnemic effects discovered and studied in psychology, we have selected those that characterize the procedural conditions of productive memorization and generalize the techniques of the logical processing of information, its fixation, and anchoring in memory. The relationship between the specified elements of the system is reflected by the formula: mnemic tasks - mnemic  effects  -   techniques  for  solving  mnemic  tasks.  The  proposed system is intended to be an information base for the development of rational strategies for intentional logical memorization of educational texts. For ease of use, its model is presented in the form of a mind map.Conclusion. As a result of the conducted research, the mnemic goal, which aims at the achievement of the process of intentional logical memorization of educational texts, has been specified, and the techniques that mediate this process have been systematized. The parameters by which systematization was carried out were a combination of certain mnemic effects. The condition for transforming the described methods into purposeful actions is the intellectual activity of students.
Keywords: memory; mnemic activity; intentional logical memorization; mnemic effects; mnemic tasks